2016
DOI: 10.18535/jmscr/v4i11.63
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Macular Edema in Diabetes

Abstract: Objective: Diabetic macular edema (DME) is the major cause of vision loss in patients with diabetic retinopathy (DR). The purpose of this study was to assess the prevalence of DME in pre diagnosed Type II diabetes mellitus cases, to analyze DME pattern based on Optical Coherence Tomography (OCT) images and to correlate it with glycemic control. Methods: In cross sectional study, 200 eyes of 100 pre diagnosed type II diabetes mellitus cases were examined for DR, DME and OCT was performed to look for central mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Our finding demonstrated that, the likelihood of developing STDR was high for both types of DM participants with longer duration of diabetes (≥10 years) and this was consistent with what has been found previously in Norway, 32 Hangzhou, China, 27 mainland China, 20 India, 34 Cameroon, 41 and Malawi 29 that longer duration diabetes was associated with the development of visionthreatening diabetic retinopathy. This might be due the fact that in diabetes there are abnormalities in energy production which are thought to be the major contributor to the development of advanced diabetic complications like STDR, and these abnormalities are considered to occur late in the development of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding demonstrated that, the likelihood of developing STDR was high for both types of DM participants with longer duration of diabetes (≥10 years) and this was consistent with what has been found previously in Norway, 32 Hangzhou, China, 27 mainland China, 20 India, 34 Cameroon, 41 and Malawi 29 that longer duration diabetes was associated with the development of visionthreatening diabetic retinopathy. This might be due the fact that in diabetes there are abnormalities in energy production which are thought to be the major contributor to the development of advanced diabetic complications like STDR, and these abnormalities are considered to occur late in the development of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of STDR among T2DM participants was 11.9% which was similar to Nepal (8.3%), 33 India (9.5%), 34 and Saudi Arabia (16.3%). 35 Nevertheless, this report was lower than Pakistan (17.6%) 36 and higher than California, USA (0.5%), 37 Pittsburgh, USA (19.0%), 38 and Slovakia (3.35).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations